Congenital Heart Disease Increases Mortality in Neonates With Necrotizing Enterocolitis - Kessler, Ulf; Hau, Eva-Maria; Kordasz, Marcin; Haefeli, Stephanie; Tsai, Catherine; Klimek, Peter; Cholewa, Dietmar; Nelle, Mathias; Pavlovic, Mladen; Berger, Steffen (Frontiers in Pediatrics, 2018)
Background: Studies on the influence of congenital heart disease (CHD) on neonates with necrotizing enterocolitis (NEC) have produced varied results. We therefore examined the influence of CHD on NEC outcomes. Methods: We carried out a retrospective single-center study including infants with confirmed NEC, treated between 2005 and 2017. We excluded patients with isolated patent ductus arteriosus (n=41) and compared outcomes of patients with hemodynamically relevant CHD (n=42) and those without CHD (n=91). Results: Patients with CHD were more mature than those without CHD (gestational age, median, 95% confidence interval (CI95), 36.9, 34.3- 37.0w, versus 32.6w, 31.9- 33.3w; P<0.01). The presence of CHD did not influence the frequencies of severe disease (overall 22% Bell stage III), nor surgical interventions (overall 30%), the occurrence of intestinal complications (overall 12%), nor the duration of hospitalization (overall 39 days in survivors). The overall mortality as well as NEC-related mortality was increased with the presence of CHD, being 48% (20 out of 42) and 14% (6 out of 42), respectively, when compared to patients without CHD, being 8% (7 out of 91) and 3% (3 out of 91). The presence of CHD and of advanced NEC stage III were independent predictors of NEC-associated fatalities with multivariate odds ratios (CI95) of 5.3, 1.1 – 26.2 for CHD (P<0.05), and of 3.4, 1.6 – 7.2 for stage III disease (P<0.01). Conclusions: While some outcome parameters in neonates with NEC remained unaffected by the presence of CHD, the mortality risk for patients with CHD was five times higher than without CHD.